Post-traumatic stress symptoms and childhood abuse categories in a national representative sample for a specific age group: associations to body mass index - Roenholt, Stine (Co-Action Publishing, 2012)
BACKGROUND: Studies of specific groups such as military veterans have found that posttraumatic stress disorder (PTSD) is linked to adverse health outcomes including unhealthy weight. The aim of this study was to examine the relationship between PTSD symptoms, experiences of childhood trauma and weight in a community sample. METHODS: A stratified random probability survey was conducted in Denmark by the Danish National Centre for Social Research between 2008 and 2009 with 2,981 participants born in 1984, achieving a response rate of 67%. The participants were interviewed with a structured interview with questions pertaining PTSD symptomatology, exposure to childhood abuse, exposure to potentially traumatizing events, height, and weight. Underweight was defined by a body mass index (BMI) <18.5, overweight was defined by a BMI ≥25 and <30 and obesity was defined by a BMI ≥30. RESULTS: PTSD symptomatology and childhood abuse were significantly associated with both underweight and overweight/obesity. Childhood emotional abuse was especially associated with underweight, whereas sexual abuse and overall abuse were particularly associated with overweight/obesity. CONCLUSION: These findings indicate that health care professionals may benefit from assessing PTSD and childhood abuse in the treatment of both overweight and underweight individuals.